G555 The maternal and neonatal microbiota correlates of preterm birth and adverse neonatal outcomes. (25th October 2020) - Adam, R; Temmerman, M; Ochieng, R; Carvahlo, M; Okiro, P; Quek, MC; Gulavi, E; Atandi, D
Abstract : Aims: Preterm birth is the leading cause of perinatal morbidity and mortality worldwide. There is a need for a better understanding of the correlation of vaginal microbiota, placenta microbiota and placental inflammatory changes with preterm birth. Necrotizing enterocolitis (NEC) is the most devastating complication of prematurity which might be caused by intestinal dysbiosis. Our study aimed to explore the vaginal microbiota, placental microbiota and histological changes in the placenta correlates with preterm labor, and determine whether fecal microbiota in premature infants differs from the term infant. Method: A case-control design was used to enroll 50 women admitted in spontaneous labor between 26 to 36 weeks and 50 controls matched for age and parity who presented in labour after 37 weeks. At birth, the infants were also enrolled. We obtained a vaginal swab from the mother prior to delivery, placenta, infant rectal swabs or stool samples. These samples were assessed using 16S ribosomal RNA (rRNA) gene sequencing. Placentas for histopathological analysis. Using a bioinformatics approach phylogeny tree was created. Beta-diversity was calculated using Permutational Multivariate Analysis of variance and Bray-Curtis dissimilarity indices were measured. Results: The vaginal microbiota in both study groups revealed a community rich in the Lactobacillus genus; 90.4% of the sample consisted of different Lactobacillus species. There were no differences in community richness of microbiota between the term and preterm groups. Preterm placentas were associated with greater rates of inflammation (43.3%) compared to term placentas (23.3%). Placenta microbial samples had a sequence read success rate of only 5.7%. Three preterm infants (7.3%) developed NEC, one (2.4%) preterm infant and one (2.4%) term infant developed gram-negative sepsis. General low yield of microbiota amongst the infants with NEC and Gram-negative sepsis in the meconium. Conclusions: There is a spectrum of diversity in vaginal microbiota of women with the term and preterm labor with no clear evidence of any specific microbiota composition patterns that are associated with preterm birth. Acute histological chorioamnionitis was associated with preterm birth. There is a lack of evidence to support the existence of a placenta microbiota. Our study supports the theory that a lack of commensal microbiota can lead to the development of NEC.